Tylogonium hoelzeli Strasser 1959 - Kime, Richard Desmond; Enghoff, Henrik (Zenodo, 2021)
99. Tylogonium hoelzeli Strasser, 1959 Distribution AT. Habitat Montane, 1100 m a.s.l.; on permafrost ground; in soil on calcareous gravel; cave, MSS. Published as part of Kime, Richard Desmond & Enghoff, Henrik, 2021, Atlas of European millipedes 3: Order Chordeumatida (Class Diplopoda), pp. 1-244 in European Journal of Taxonomy 769 on page 47, DOI:10.5852/ejt.2021.769.1497, http://zenodo.org/record/5536353